beta-Glucan extracted from the medicinal mushroom Agaricus blazei prevents the genotoxic effects of benzo[a]pyrene in the human hepatoma cell line HepG2 - Friedmann Angeli, Jose Pedro; Ribeiro, Lúcia Regina [UNESP]; Bellini, Marilanda Ferreira; Mantovani, Mario Sergio (Springer, 2009)
The mushroom Agaricus blazei is studied for its nutraceutical potential and as a medicinal supplement. The aim of the present study was to investigate the chemoprotective effect of beta-glucan extracted from the mushroom A. blazei against DNA damage induced by benzo[a]pyrene (B[a]P), using the comet assay (genotoxicity) and micronucleus assay with cytokinesis block (mutagenicity) in a human hepatoma cell line (HepG2). To elucidate the possible beta-glucan mechanism of action, desmutagenesis or bioantimutagenesis types, three treatment protocols were tested: simultaneous, pre-treatment, and presimultaneous. The results showed that beta-glucan does not exert genotoxic or mutagenic effect, but that it does protect against DNA damage caused by B[a]P in every protocol tested. The data suggest that beta-glucan acts through binding to B[a]P or the capture of free radicals produced during its activation. on the other hand, the pre-treatment results also suggest the possibility that beta-glucan modulates cell metabolism.
Keywords: beta-Glucan; Comet assay; Micronucleus assay; HepG2; Antigenotoxicity; Antimutagenicity